(untitled) (Docentes 2.0 Journal, 2020)
This work was developed with the purpose of manufacturing a portable hydraulic pumps test bench for didactic applications in order to study the flow of fluids and their characteristics, in which he was able to develop practical experiences in the engineering area, knowing how to handle it in the labor and industrial environment the behavior of this, Therefore this developed work was supported by theories of Pumps, Theory, Design and applications, Maxtais (2009), Science of materials, Smith (2001), Strength of Materials, Mott ( 2009), Introduction to Engineering, White (2011). On the other hand, the present investigation was found in the feasible type of project, therefore the data collection technique was used, such as the management of statistical techniques, direct observation, among others. Finally, practical procedures were carried out for the construction of the pilot plant, such as the parameterization of its design, the selection of both materials and equipment, as well as the design of this reflected in dimensioned plans with the use of AutoCAD 2015 ®, developing in this way the 5 stages or phases of the manufacture of this study tool which were validated by reason of the operating pressure, performance, head, and robustness of it.